THEORETICAL REVIEW OF ISLAMIC LEGAL SOURCES ACCORDING TO THE MISREPRESENTATION THEORY OF HALLAQ - Rahmat Budiman (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2020)
The existence of Islamic law from time to time in a Muslim community is believed to be the result of an in-depth study of the sources of Islamic law: the Qur’an (the Word of God), Hadith (sayings of the Prophet Muhammad), Ijtihad (the process of making a legal decision by independent interpretation of the legal sources, the Qur’an and the Sunnah), Qiyas (the deduction of legal prescriptions from the Qur’an or Sunnah by analogic reasoning), as well as Ijma (the result of the agreement of the Scholars). These sources of Islamic law were then poured into Usul al-Fiqh, which was then considered as a concrete form of Islamic law itself. This is reinforced by the classical teachings of orientalist Scholars who acknowledge that Islamic law is preserved in Usul al-Fiqh by great Scholars. However, this concept was challenged by Hallaq with a misrepresentation of his theory. He stated that Sharia can exist in society, not because of the role of Usul al-Fiqh but the role of the Fatwa (authoritative legal opinion), which is given by the Mufti and is applied by practitioners of Islamic law in Muslim-majority societies. Abstrak: Eksistensi hukum Islam dari masa ke masa di suatu komunitas muslim diyakini sebagai hasil kajian mendalam dari sumber Hukum Islam berupa Al- Quran, Hadist, Ijtihad, Qiyas, maupun berupa hasil kesepakatan para ulama (Ijma). Sumber – sumber hukum Islam ini kemudian dituangkan ke dalam Ushul Fiqh yang kemudian dinaggap sebagai wujud konkrit dari hukum Islam itu sendiri. Hal ini diperkuat oleh ajaran – ajaran klasik para sarjana orientalis yang mengakui bahwa hukum Islam dipelihara di dalam Ushul Fiqh karya ulama – ulama besar. Namun konsep ini mendapat tentangann dari Hallaq dengan misrepresntasi teorinya. Hallaq menyatakan bahwa Syariah dapat eksis di masyarakat bukan karena peranan dari Ushul Fiqh namun karena adanya peranan Fatwa yang dihidupkan oleh Mufti, dan diaplikasikan oleh para praktisi Hukum Islam di masyarakat mayoritas Islam. Kata Kunci: Sumber Hukum Islam, Syariah, Ushul Fiqh, Mufti, Fatwa